The European rules of Civil Procedure: a starting point for civil procedure harmonisation? - Gascón Inchausti, Fernando (CUADERNOS DE DERECHO TRANSNACIONAL, 2021)
In autumn 2020, the European Law Institute and UNIDROIT approved the European Rules of Civil Procedure, a systematic set of rules through which a civil process model is designed with the potential to be operational in any European country. It is obviously a soft law instrument, which is based on an extensive and prolonged work of legal comparison, which has made it possible to detect the best solutions to the needs of an efficient civil justice system today. This contribution analyses what the European Rules are and what they are not, along with the essential features of the civil procedural model designed, characterized by flexibility, case management and a sustained effort for the consensual solution of the dispute. It is difficult to predict what their future impact will be, although the European Rules of Civil Procedure are certainly called upon to play a relevant role in any task of civil procedural harmonisation that is undertaken in the future, to the extent that they have shown that it is technically possible and that, therefore, that it depends primarily on political variables.
Keywords: European Rules of Civil Procedure; ELI/UNIDROIT Project; model rules; civil procedure harmonisation; comparative civil procedure; case management.